Diagnosis of vestibular schwannoma in modern clinical practice - Żebrowska, Małgorzata; Nawrocki, Adam; Kucharski, Andrzej; Konopelko, Michał; Trojanowski, Piotr; Klatka, Janusz (Journal of Education, Health and Sport, 2019)
The auditory nerve tumor is the most common tumor of the cerebellopontine angle region (CPA). The use of modern diagnostic methods allows to detect the tumor at an early stage of development, and consequently, the possibility of effective treatment. The clinical features and the most effective diagnostic procedures are presented.